The deletion of chiMaD1, a horizontally acquired chitinase of Metarhizium anisopliae, led to higher virulence towards the cattle tick (Rhipicephalus microplus). Issue 12 (8th June 2021) - Sbaraini, Nicolau; Junges, Ângela; de Oliveira, Eder Silva; Webster, Anelise; Vainstein, Marilene Henning; Staats, Charley Christian; Schrank, Augusto
ABSTRACT: The first line of the Arthropods defense against infections is the hard-structured exoskeleton, a physical barrier, usually rich in insoluble chitin. For entomopathogenic fungi that actively penetrate the host body, an arsenal of hydrolytic enzymes (as chitinases and N-acetylglucosaminidases), that break down chitin, is essential. Notably, twenty-one putative chitinase genes have been identified in the genome of Metarhizium anisopliae, a generalist entomopathogenic fungus. As a multigenic family, with enzymes that, presumably, perform redundant functions, the main goal is to understand the singularity of each one of such genes and to discover their precise role in the fungal life cycle. Specially chitinases that can act as virulence determinants are of interest since these enzymes can lead to more efficient biocontrol agents. Here we explored a horizontally acquired chitinase from M. anisopliae, named chiMaD1 . The deletion of this gene did not lead to phenotypic alterations or diminished supernatant's chitinolytic activity. Surprisingly, chiMaD1 deletion enhanced M. anisopliae virulence to the cattle tick ( Rhipicephalus microplus ) larvae and engorged females, while did not alter the virulence to the mealworm larvae ( Tenebrio molitor ). These results add up to recent reports of deleted genes that enhanced entomopathogenic virulence, showing the complexity of host-pathogen interactions. Abstract : Deletion of the chitinase gene chiMaD1 in the enthomopathogenic fungus Metarhizium anisopliae increases virulence towards the cattle tick Rhipicephalus microplus.